2007
DOI: 10.1007/s00464-006-9153-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of bile duct sludge: is it different from bile duct stones?

Abstract: The findings indicate that the clinical significance of symptomatic BDS is similar to that of CBD stones. Bile duct sludge seems to be an early stage of choledocholithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
(51 reference statements)
1
6
1
Order By: Relevance
“…Sludge and stones in the bile ducts of symptomatic patients have similar clinical significance, therefore requiring endoscopic clearance. 27 Accuracy of sphincterotomy is superior to cholangiographic image by ERCP for choledocholithiasis. To our knowledge, all series of MRCP reported have compared the MRCP results with cholangiographic results as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Sludge and stones in the bile ducts of symptomatic patients have similar clinical significance, therefore requiring endoscopic clearance. 27 Accuracy of sphincterotomy is superior to cholangiographic image by ERCP for choledocholithiasis. To our knowledge, all series of MRCP reported have compared the MRCP results with cholangiographic results as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MRCP and other non‐invasive biliary imaging modalities often miss biliary sludge. This may cause symptoms and often is only visible after either sphincterotomy or surgery 22 . The data from the present series, however, indicates that there is a group of patients presenting with biliary disease who have spontaneously passed a bile duct calculus as demonstrated on clinical, biochemical, and radiological (US and MRCP) grounds.…”
mentioning
confidence: 50%
“…In addition, one study demonstrated that small stones ,8 mm in size can pass through the duodenal papilla [14]; this may also contribute to non-dilated bile ducts. In a study of the clinical significance of bile duct sludge, Keizman et al [15] reported that bile duct sludge is regarded as an early state of choledocholithiasis because 16% of patients with CBD sludge developed symptomatic CBD stones. In addition, CBD dilatation was less commonly observed in the patients with sludge in their study.…”
Section: Discussionmentioning
confidence: 99%